(untitled) (Baghdad Science Journal, 2025)
Five N-substituted poly diimides were prepared by two steps. First step was included the preparation of five N-substituted diamides by reaction of adipoyl chloride with different amines .The second step was involved reaction of diamides with poly acryloyl chloride to obtain five new poly diimides having different physical properties which may used in different applications.